Assessment of Eggplant (Solanum melongena L.) Genotypes and Selection of Parameters for Better Yield - Jelena Damnjanović; Zdenka Girek; Jelena Milojević; Veselinka Zečević; Tomislav Živanović; Milan Ugrinović; Suzana Pavlović (Chemistry Proceedings, 2022)
One of the goals in eggplant breeding (Solanum melongena L.) is higher yield. This study included 20 different genotypes that are part of the collection of the Institute for Vegetable Crops Smederevska Palanka. Sixteen genotypes originated from Serbia, two originated from the Netherlands, one originated from Italy, and one originated from Israel. The experiment was conducted at Vranovo (44°36′6.35″ N, 20°59′55.47″ E, altitude 87 m) using a randomized complete block design and three replications. The yield parameters (earliness, plant height/centimeter, number of fruits per plant, fruit weight/gram, fruit length and width/centimeter, and fruit yield per genotype/kilogram) were examined to study the relationships among traits and their effects on eggplant yield. The number of fruits per plant had a positive and significant correlation with yield (r = 0.685 **). Additionally, the results showed positive correlations between plant height and fruit length (r = 0.812 **), between plant height and fruit weight (r = 0.147), and between fruit width and fruit weight (r = 0.523 *). These characteristics had direct or indirect positive effects on yield, so they can be used as selection criteria to increase the final yield of eggplant. Because there is genetic variability between the tested genotypes, progress in breeding will depend on this variation. Earliness had a negative correlation with yield (r = −0.044) and with all other parameters.